The role of indole-3-acetic acid transport and the effect of girdling on the calcium nutrition and quality of `Sunlite' nectarine fruits - Wand, Stephanie J. E.(Stephanie Juliane Editha) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1990.